Effect of external electric field on morphology, structure and optical properties of β-Ga2O3 microstructures grown by CVD method. (September 2020) - Zhao, Shuang; Feng, Qiuju; Gao, Chong; Wang, Deyu; Xing, Yan; Xie, Jinzhu; Dong, Zengjie; Li, Mengke; Liang, Hongwei
Abstract: Uniform and regularly arranged β-Ga2 O3 microstructures were grown on patterned sapphire substrates (PSS) by the external electric field assisted chemical vapor deposition method at applied voltages in the range of 0–80 V. It was found that the voltage has a significant effect on the growth rate, surface morphology and crystalline quality of β-Ga2 O3 . When the external voltage increases, the β-Ga2 O3 growth rate on the PSS increases and the crystal quality improves. When the external voltage is 80 V, a β-Ga2 O3 thin film with high crystalline quality was obtained. Furthermore, the absorption spectra indicated that the absorption edge of the samples showed a blue shift with increasing external voltage. These results show that the crystal quality of the sample was improved after applying an external electric field. Highlights: A uniform and regularly arranged β-Ga2 O3  microstructures was grown on PSS by external electric field assisted CVD. When the external voltage is 80 V, β-Ga2 O3 thin film with high crystalline quality was prepared. The crystal quality of the β-Ga2 O3 being improved after the external electric field.